Pemanfaatan Limbah Kulit Rambutan Menjadi Produk Teh di Desa Karang Bayan Kecamatan Lingsar Kabupaten Lombok Barat - Vina Melsa Daiyanti; Nurul Aini; Baiq Intan Nurhaliza; Doni Kurnia Purwanto; Agus Ramdani (Jurnal Pengabdian Magister Pendidikan IPA, 2023)
The skin of rambutan, which has only been considered as waste by the community, has many health benefits. These benefits include being a natural antibacterial against bacteria, being able to fight free radicals, being a natural antioxidant, as a medicine for dysentery and fever, can increase the body's immunity, and can be used as an antidiabetic and antihypercholesterol agent. This activity aims to utilize rambutan skin waste into a tea product. This activity was carried out in Karang Bayan Village, Lingsar District, West Nusa Tenggara. Learning by Doing is used in this activity in which the University of Mataram's Integrated Real Lecture Work (KKN) team learns through the practice of processing rambutan peels into tea directly by utilizing existing tools and materials so that it is more effective and efficient in the outcomes of KKN activities in Karang Bayan Village . The result of the implementation of the Integrated Real Work Lecture (KKN) activities is to provide innovation and knowledge about the utilization of rambutan peel waste. It is hoped that in the future the community will be able to manage rambutan peel waste into a creative economic business, be able to develop creativity in converting unused waste into herbal teas that have many benefits. In addition, this activity is also able to be an alternative in reducing waste, especially rambutan skin waste.